PENGEMBANGAN MODEL PEMBELAJARAN SIMPLE BASKETBALL PADA SISWA SEKOLAH MENENGAH ATAS LUAR BIASA TUNAGRAHITA DHARMA MULIA SEMARANG TAHUN 2015 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of the study is to find out the product of learning model development of semple basketball for eleventh grade students in Mentally Disabled-Extraordinary Senior High School Dharma Mulia Semarang.Based on the study of the first try out, it was obtained 84% (good), from the expert’s evaluation it was obtained 87.5% (good). The result of the second try out was 87.43% (good). From the first and the second try out there is significantly increase 3.43%. Based on the product study, it can be concluded that the learning model development of simple basketball can be used as an alternative model in learning health, physical, and recreation education for eleventh grade students in Mentally Disabled-Extraordinary Senior High School Dharma Mulia Semarang. The suggestion for the health, physical, and recreation education teacher in Mentally Disabled-Extraordinary Senior High School Dharma Mulia Semarang is to make interactive learning model by using simple basketball game in learning basketball.